(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research paper examines the effectiveness of human resource management (HRM) practices in hospitals within Nashik City and their impact on employee satisfaction. Utilizing a quantitative research approach, data was collected from a sample of 200 hospital employees through structured questionnaires. The study assessed various HRM practices, including recruitment and selection, training and development, performance evaluation, employee engagement, and alignment with organizational goals. The findings indicate that employees perceive these HRM practices as highly effective. Additionally, specific practices such as regular feedback, opportunities for career advancement, work-life balance support, effective communication, and employee involvement were found to significantly enhance employee satisfaction. These results emphasize the crucial role of HRM in shaping employee perceptions and well-being in hospital settings.